7 Social Media Lessons To Make Your Corporate Communications Trustworthy - Cohen, Heidi (Communication & Language at Work, 2014)
Do your corporate communications suffer from a lack of trust by your target audience? If so, your marketing professionals can benefit from these seven social media lessons that help guide you towards making your communications more trustworthy.